The relationship between inflammatory bowel disease and sarcopenia-related traits: a bidirectional two-sample mendelian randomization study - Sun, Zhihuang; Liu, Guangwei; Xu, Jiajia; Zhang, Xianyu; Wei, Huahua; Wu, Guobao; Jiang, Jian (Frontiers in Endocrinology, 2024)
Objective Observational studies have revealed a link between inflammatory bowel disease (IBD) and sarcopenia. However, it remains unclear whether this correlation between IBD and sarcopenia is causal. Methods The genetic instrumental variables (IVs) associated with IBD and sarcopenia-related traits were derived from publicly available genome-wide association studies. We employed a two-sample bidirectional Mendelian randomization (MR) method. we obtained genetic IVs for five phenotypes from 34,652 cases in IBD, 27,432 cases in ulcerative colitis (UC), 212356 cases in crohn’s disease (CD), 9336415 cases in low hand grip strength (LHGS), and 450243 cases in appendicular lean mass (ALM), respectively. The inverse variance weighting and other MR methods were used to explore the bidirectional causal relationship. Furthermore, we performed heterogeneity test, pleiotropy test, leave-one-out sensitivity test, and multivariate MR to evaluate the robustness of the results. Results The forward MR results showed that the UC (OR=0.994, 95% CI: 0.9876–0.9998, P = 0.044) and CD (OR=0.993, 95% CI: 0.988–0.998, P = 0.006) was negatively correlated with ALM. In the reverse MR analysis, we also found that LHGS was negatively correlated with the IBD (OR=0.76, 95% CI: 0.61–0.94, P = 0.012) and CD (OR=0.53, 95% CI: 0.40–0.70, P <0.001). Besides, genetically predicted higher ALM reduced IBD (OR=0.87, 95% CI: 0.79–0.95, P = 0.002), UC (OR=0.84, 95% CI: 0.76–0.93, P = 0.001), and CD (OR=0.87, 95% CI: 0.77–0.99, P = 0.029). However, the results of other MR Analyses were not statistically different. Conclusions We found genetically predicted UC and CD are causally associated with reduced ALM, and higher hand grip strength reduced IBD and CD risk, and higher ALM reduced IBDs risk. This MR study provides moderate evidence for a bidirectional causal relationship between IBD and sarcopenia.